2000
DOI: 10.12968/bjon.2000.9.22.5418
|View full text |Cite
|
Sign up to set email alerts
|

NHS Direct: issues for education, management and research

Abstract: The NHS Plan (Department of Health (DoH), 2000) specifically highlights the role of NHS Direct in its vision of a health service designed around the patient. Despite this, the new nurse-led service has come under critical attack. NHS Direct is in the process of developing an evidence base to underpin its practice. It is recognized that telephone management skills are important clinical skills and while decision support computer software can help elicit an appropriate client history, the interpersonal skills ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although TN is based on the nursing process, the application in practice is not well‐understood (Wheeler & Windt 1993, Rutenberg 2002, Peck 2005, AAACN, 2007). Some programmes do provide training (e.g., National Health Services Direct, Glasper et al. 2000), but this has been found to be of limited value because of reliance on protocols rather than an in‐depth understanding of the TN process (Greatbatch et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although TN is based on the nursing process, the application in practice is not well‐understood (Wheeler & Windt 1993, Rutenberg 2002, Peck 2005, AAACN, 2007). Some programmes do provide training (e.g., National Health Services Direct, Glasper et al. 2000), but this has been found to be of limited value because of reliance on protocols rather than an in‐depth understanding of the TN process (Greatbatch et al.…”
Section: Introductionmentioning
confidence: 99%
“…Education and auditing of the triage process for the triage nurses may be essential for successful management of the telephone triage system. 13,14 New nurses are trained by lecture for 2 weeks, by on-the -job training with an educator for 2 weeks and have their skills checked by a physician twice. At telephone triage there may be many kinds of patients, including some reluctant patients.…”
Section: Discussionmentioning
confidence: 99%
“…reported that they emphasized communication through role play in telephone nurse education courses. 14 In our education course, nurses are educated through role play with many different kinds of cases, including reluctant patients. The triage process was audited by nurses and doctors from the triage quality review board.…”
Section: Discussionmentioning
confidence: 99%